Penerapan Metode Ant Colony Optimization Untuk Menentukan Jalur Distribusi Di PT. Indomarco Adi Prima - Lisdiarto, Andi; Winarti, Wiwin (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
PT. Indomarco Adi Prima is an Indofood distribution unit company that handles the largest basic necessities with product variations such as Indomie, Bimoli, Blue Triangle, and so on. To distribute goods to PT. Indomarco Adi Prima (Stock Point Sampang), is still experiencing problems in determining the best route in sending goods to distributor store locations. From this problem, it is necessary to have a method that can optimize the distribution route of goods at PT. Indomarco Adi Prima (Stock Point Sampang), which aims to streamline time, energy and operational costs of shipping goods. The Ant Colony Optimization (ACO) algorithm is a methodology produced through the observation of ants. Each ant is assigned to find a solution to an optimization problem, one of which is the Traveling Salesman Problem (TSP). Where this research starts from PT. Indomarco Adi Prima (Sampang Stock Point) to 5 distributor store locations, namely with point (A) PT. Indomarco Adi Prima (Sampang Stock Point), point (B) Padang Store, point (C) Pojok Kaliterus Store, point (D) Artomoro Mart, point (E) RM. Taman Sari Rasa & Waterpark, point (F) Tammy Mart and back again to point (A) PT. Indomarco Adi Prima (Sampang Stock Point). By doing calculations using the ACO algorithm, either using analytical techniques or using the matlab application, the most optimal distribution path route is produced, on the 20th route, starting from point (A) - (B) - (C) - (D) - (E) - (F) - (A) and vice versa from point (A) - (F) - (E) - (D) - (C) - (B) - (A) with a total route length of 38.5 KM with a Pheromone result of 0.0260.